Resilience by Design: Site Reliability Engineering for Multi-Cloud Systems - Allam, Hitesh (International Journal of Emerging Research in Engineering and Technology, 2022)
Companies are rapidly using multi-cloud architectures in the modern digital world in order to improve their enhanced performance, reduce vendor lock-in, and increase flexibility. This change brings further challenges, particularly in terms of guaranteeing consistency, resilience, and stability throughout many several cloud platforms. This article investigates how Site Reliability Engineering (SRE) may be a strategic framework for addressing these kinds of challenges by including resilience into the basic design of multi-cloud systems. Emphasizing Site Reliability Engineering's (SRE) focus on automation, observability, and proactive problem management, this article offers an overview to the concepts and approaches of SRE. Resilience is not only useful but also a necessary feature for distributed, cloud-native applications operating in different environments, the research underlines The primary goal is to show how SRE serves as both a mindset and a method for building fault-tolerant systems competent of adjusting to and recovering from disruptions with least influence on user experience. To build strong infrastructure, we describe our approach which combines error budgets, service-level goals (SLOs), chaotic engineering, and thorough monitoring. Examining a worldwide company using applications on AWS, Azure, and Google Cloud, this case study offers insights on deployment challenges, dependability strategies, and SRE-driven strategy impacts. The studies show considerable increases in system availability, recovery times & operational effectiveness. In the end, our findings confirm that intentional design and thorough engineering lead to resilience more rather than reactive solutions. This article offers a methodology for companies trying to harness the benefits of multi-cloud ecosystems while guaranteeing high service dependability, therefore orienting resilience as a fundamental design aspect rather than a side issue